Information system on microbial collections as a part of bioresource collections portal for Russia’s FASO organizations: a working protocol - F. V. Kazantsev; A. A. Smirnova; A. S. Rozanov; Yu. E. Uvarova; D. A. Afonnikov; S. E. Peltek; S. A. Lashin (Вавиловский журнал генетики и селекции)
Nowadays, many scientific organizations of Russia own collections of microorganisms on which large volumes of information have been generated. These data represent the descriptions of objects of diverse nature (bacteria, archaea, fungi, protists) and their properties, which have been carefully collected and cataloged by generations of researchers. Not every organization that has such collections has an open access electronic catalog, which not only complicates work with these unique materials, but also even hides the fact of the existence of such collections. This state of affairs requires the development of electronic resources for presenting these materials to the scientific community. To put together the information on microorganism collections, we have developed an internet portal (http://www.biores.cytogen.ru/microbes/) of microbial bioresource collections of FASO organizations in the Russian Federation. The portal was created under the project developing the information system for bioresource collections of FASO institutes. It is a platform where collection organizations can place information about the storage units of their collections, as well as other information on collections, including links to their own catalogs. In this paper, we describe the principles of working with the portal. The portal’s graphical interface allows users, both registered and unregistered, to receive the following information about collections of microorganisms: a list of collections represented in the database, contact details of the organization and information about the curator of the collection, summary statistics for each collection, as well as information on storage units. Registered users – owners of collections – have the opportunity to create and modify records about the storage units of their collections, and to update their description. To automate work with the portal, software access to the database through the REST API has been implemented (http://api.biores.cytogen.ru/ microbes/). At present, the portal is still being filled, but it already contains a description of more than 13,000 items of storage (of which 3500 are in the microorganisms’ part) of 65 bioresource collections in Russia’s FASO organizations. Of these collections, 12 with microorganisms have a total diversity of funds of about 50,000 strains).